Design of Microcontroller Based Wireless Controlled Animatronic Hand - Shajith Ali U, Venkatakrishnan S, Saisrinivasan R, Patrick.A.Joseph (International Journal of Advanced Science and Technology, 2020)
This paper aims in explaining about the project “Wireless Controlled Animatronic Hand” which is a device which copies the motion of a real human and controls a prosthetic hand wirelessly. This paper also focuses on the designing of the prosthetic hand, the control of the prosthetic hand, the way of communication between the two physically isolated systems and the interfacing between the microcontroller and the external components. This project was carried with the primary initiative to serve the handicapped people and to develop an efficient product at an affordable rate.